Performance of spring maize (Zea mays L.) varieties under varying plant rectangularity and fertility levels - Sharma, Ashu; Kachroo, Dileep; Puniya, R.; Sharma, Neetu; Mahajan, Amit; Stanzen, Lobzang (Annals of Agricultural Research, 2016)
A field experiment was conducted during spring season of 2013 to study the effect of plant rectangularity varieties and fertility levels on growth, yield and quality of spring maize. Among spacing, S2 recorded significantly higher dry matter accumulation, number of grains/cob and 1000- grain weight than S1. Significantly higher grain and stover yield of spring maize was produced when planted at closer spacing 60Ã—20 cm. PMH -1 recorded significantly higher plant height, dry matter accumulation, number of grains/cob, 1000-grain weight, grain and stover yield than JH- 3459. Application of N140P30.57K29.17 kg/ha being at par with N120P26.20K25 kg/ha which produced significantly higher plant height, dry matter accumulation, number of grains/cob, 1000-grain weight, grain and stover yield than N80P17.47K16.67 kg/ha and N100P21.83K20.83 kg/ha. However, the protein content was found higher in N140P30.57K29.17 kg/ha level, which was at par with N120P26.20K25 kg/ ha level, whereas starch content was significantly higher in N80P17.47K16.67 kg/ha.